Travelers hostel design: does spatial organization affect the privacy referring to Islamic concept and principle? - Zulkifli, Fatimah Najah; Ahmad Noorhani, Nur Maizura; Mustapha, ArniatulAiza; Khalil, Khainina (Universiti Teknologi MARA, Kelantan, 2018)
This paper illustrates the background of Islamic concepts and principles used to describe the basic framework of privacy on spatial design for traveler’s hostel. This paper also reviews the theoretical views in establishing the element of privacy for Muslim guests in traveler’s hostel according to Syariah. According to Oliveira-Brochadoa [19] states there is a huge problem between Travelers’ Behavior with Hostel’s Spatial Organization relationship in terms of lack of privacy, safety of belongings, how to cater the space to feels comfortable with more privacy, socializing space and the design that reflect the culture. Hence, this paper is to define the personal space concerning to the traveler’s privacy according to Syariah that affect the spatial organization. Moreover, this paper intends to reveal the privacy elements that are vital and may contribute for traveler’s hostel in achieving a more conclusive research on spatial design focusing on the Syariah and Muslim guests. It involves a few research methodologies that require the researcher to study on the Islamic concept and principles that needed to create more efficient space in terms of personal space, safety and security element, social interaction and space relationship elements. The results of this study could shed useful insights in providing privacy for travelers in a small budget accommodation.With that, by introducing the separateness space according to Syariahcompliant hostel concept among budget hostel operators may give an alternative to Muslim traveler in Malaysia.